PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK ETANOL DAN FRAKSI ETANOL, FRAKSI KLOROFORM, FRAKSI N-HEKSANA, FRAKSI AIR, FRAKSI ETIL ASETAT DARI DAUN BAWANG DAYAK (Eleutherine palmifolia (L.) Merr.) - Eka Kumalasari; Arini Septia; Dwi Rizki Febrianti; Noor Aisyah (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2023)
Dayak onion (Eleutherine palmifolia (L.) Merr.) is one of the typical Central Kalimantan plants that has been hereditary used by Dayak people as traditional medicine. Generally, only parts of dayak onion bulbs are used while the onion leaves are often discarded and rarely used. Dayak onion leaves contain secondary metabolites, one of them is flavonoids. Flavonoid compounds have many benefits, namely as an antioxidant, antibacterial, antiviral, anti-inflammatory, anti-allergic and anticancer. The purpose of this study was to determine the total flavonoid content contained in etahanol extraction, n-hexane fraction, chloroforom fraction, ethyl acetate fraction, 70% ethanol fraction and dayak onion leaf water fraction. Extraction of onion dayak leaves using maceration method with 70% ethanol as solvent. After extraction the fraction is carried out with a liquid-liquid extract method and different polarity of solvent. The product of extraction and fractionation were measured using UV-Vis spectrophotometry.The quantitative analysis of total flavonoid content from the highest level of onion dayak fraction chloroform fraction 85,478% ± 0,0019, then n-hexane fraction 60,171% ± 0,0010, water fraction 32,671% ± 0,0005, ethyl acetate fraction 27,934% ± 0, 0002, 70% ethanol extract 15,348% ± 0,0001, and the lowest ethanol 70% fraction 10,104% ± 0,0003.